PENINGKATAN HASIL BELAJAR IPA MELALUI PENGGUNAAN MODEL PROJECT BASED LEARNING KELAS V SDN LEUWIMUNDING - Kurnia Nurul Fuji Astuti; Nurkholis; Fitri Aprianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Learning outcomes is competences that student get after study. One of factor that determine learning outcome is motivation, where it’s take main role of student it self. Teacher must create learning condition that can motivate student. The researcher choose one of learning model that is Project Based Learning (PjBL) that will increase student motivation then influence to the learning outcome it self. This research is a classroom action research Kemmis & Mc.Taggart model which aim to increase learning outcomes student of class 5 through using Project Based Learning model. This research implemented in 2 cycle. In every cycle using lesson study step which is planning, do, see and reflection. The subject on this research is student of 5 class SDN Leuwimunding I with student total 33 students which is include 23 male student and 11 female student. Instrument research is using test, observation and interview. Analysis data is using quantitative percentage. The result show that using Project Based Learning model can improve student learning outcome in class 5 on water cycle subject material. The increasement is mark by student learning outcome increase with 87,88% with 80,75the average, so it is 85% reach the result with ≥70 minimum completeness criteria. Keyword : student learning outcome, Project Based Learning model, water cycle.